Reproductive Strategy and Occurence of Gametophytes of Thai Laver Porphyra vietnamensis Tanaka et Pham-Hoang Ho (Bangiales, Rhodophyta) from Songkhla Province - Ruangchuay, Rapeeporn; Notoya, Masahiro (Agriculture and Natural Resources, 2007)
Reproductive strategy and occurrence of gametophyte phase of Thai laver Porphyra vietnamensis Tanaka et Pham-Hoang Ho were investigated to provide further information for aquaculture. The study was weekly evaluated in two localities of rocky dike; Leam Son-on and Ban Pak Bang Sakhom in Songkhla province during October 1999 to March 2000. Gametophytes, 1.48 (± 0.18) cm in length and 0.42 (± 0.05) cm in width, were visually appeared in early December on the upper level of the dike of both stations. The mature thalli were linear, broad linear or lanceolate, 4.49 (± 0.58) cm in length and 0.75 (± 0.18) cm in width. Speramatangia and zygotosporangia were generally observed from the same plant in early January with size of 10.78 (± 1.68) cm in length and 1.40 (± 0.11) cm in width. Most of them were linear, broad linear or lanceolate in shape. Spermatangial division was 64 (a/4, b/4, c/4) and 32 (a/2, b/4, c/4). While, zygotosporangia division was 8(a/2, b/2, c/2). Biomass was increased to 5.79 and 5.77 g wet weight /100 cm2 at Leam Son-on and Ban Pak Bang Sakhom respectively. Archeosporangia were observed in small thalli, 1-3.8 cm in length and 1.1-1.5 cm in width, in late March. The occurrence of gametophytic phase of P. vietnamensis from the two sampling stations was similar. The new populations could be observed at both stations during the sampling time.